COVID-19 vaccine Mandates: An Australian attitudinal study. Issue 51 (5th December 2022) - Attwell, Katie; Rizzi, Marco; McKenzie, Lara; Carlson, Samantha J; Roberts, Leah; Tomkinson, Sian; Blyth, Christopher C.
Abstract: Background: The rollout of vaccines against COVID-19 is prompting governments and the private sector to adopt mandates. However, there has been little conceptual analysis of the types of mandates available, nor empirical analysis of how the public thinks about different mandates and why. Our conceptual study examines available instruments, how they have been implemented pre-COVID, and their use for COVID-19 globally. Then, our qualitative study reports the acceptability of such measures in Western Australia, which has experienced very limited community transmission, posing an interesting scenario for vaccine acceptance and acceptability of measures to enforce it. Method: Our conceptual study developed categories of mandates from extant work, news reports, and legislative interventions globally. Then, our empirical study asked 44 West Australians about their attitudes towards potential mandatory policies, with data analysed using NVivo 12. Results: Our novel studies contribute richness and depth to emerging literature on the types and varying acceptability of vaccine requirements. Participants demonstrated tensions and confusion about whether instruments were incentives or punishments, and many supported strong consequences for non-vaccination even if they ostensibly opposed mandates. Those attached to restrictions for disease prevention were most popular. There were similar degrees of support for mandates imposed by employers or businesses, with participants showing little concern for potential issues of accountability linked to public health decisions delegated to the private sector. Participants mostly supported tightly regulated medical exemptions granted by specialists, with little interest in religious or personal belief exemptions. Conclusion: Our participants are used to being governed by vaccine mandates, and now by rigorous lockdown and travel restrictions that have ensured limited local COVID-19 disease and transmission. These factors appear influential in their general openness to COVID-19 vaccine mandates, especially when linked explicitly to the prevention of disease in high-risk settings.